Aplikasi Akademik pada TKQ Al-Mukaramah - Nadila Fauzani Mulqi; Riki Purba; Novita Anggraini (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Al-Mukaramah Sukajadi Quran Kindergarten (TKQ) does not yet have a school academic information system for structured data processing activities for teachers, students and female students. TKQ Al-Mukaramah really needs an information system in the form of a website application to improve the school's academic system in an era of increasingly developing technology in Indonesia, Al-Mukaramah Sukajadi Al-Quran Kindergarten (TKQ) which currently does not have an academic information system in the form of a web-based application , so there are still many deficiencies in academic information technology. The solution used in this research is the creation of a school web-based application as a structured data processing method at TKQ Al-Mukaramah. This website application was created using UML methods such as UseCase, Activity Diagram, Sequence Diagram, and Class Diagram. With Sublime tools with PHP and MySql programming languages. And the development model used is the Prototype model. By implementing this academic website application at Al-Mukaramah Al-Quran Kindergarten (TKQ), it can make it easier for teachers and students to be able to view school data quickly, and effectively.